High-level periodic conjugated terpolymers through AA/BB monomer pair-type terpolymerization improve performance of polymer solar cells. (February 2023) - Jung, Sungwoo; Cho, Yongjoon; Ji, Yutong; Oh, Jiyeon; Park, Geunhyung; Kim, Wonjun; Jeong, Seonghun; Lee, Sang Myeon; Chen, Shanshan; Zhang, Youdi; Yang, Changduk
Abstract: With a growing interest in developing high-performance π-conjugated terpolymers via random terpolymerization, new synthetic approaches resulting in higher-quality terpolymers with improved backbone regularity are needed to help make organic optoelectronic and photovoltaic applications more prosperous. Herein, we report an AA/BB monomer pair-type terpolymerization protocol that renders semi-sequence-controlled (SSC) terpolymers by polymerizing the aperiodically repeating units into the preferentially formed periodic, alternating polymeric block sequences, unlike the conventional random terpolymerization for producing terpolymers with irregular repeating sequences. A close comparison of SSC- and conventional terpolymerization-derived terpolymers indicate detectable differences in the absorption, energetic properties, carrier transport, energy loss, and morphological characteristics. The optimal SSC terpolymer-based polymer solar cells (PSCs) outperform the conventional terpolymerization-derived counterparts in power conversion efficiency (PCE). Moreover, the optimal SSC terpolymer-based PSCs processed by an eco-friendly solvent/additive system also exhibit outstanding PCEs of 16.52 % (small area of 0.041 cm 2 ) and 15.50 % (large area of 1 cm 2 ). To the best our knowledge, it is the highest value among tetrahydrofuran-processed PSCs. This SSC terpolymerization shows considerable promise in synthesizing high-quality in-chain terpolymers with high backbone sequence control without sacrificing their inherent beneficial features, providing high potential for further improving their PSC performances. Graphical Abstract: ga1 Highlights: A new synthetic approach for random terpolymerization using semi-sequence-controlled (SSC) method is demonstrated. The SSC method can tune the optical properties, energy levels, and electrical characteristics of random terpolymers. The optimal SSC terpolymer results in photovoltaic performance characteristics superior to those of the conventional terpolymer. High efficiency of 16.52 % is achieved for optimal SSC terpolymer-based polymer solar cells processed by an eco-friendly solvent. This work can provide a simple and effective tool for the sustainable synthesis of high-quality in-chain terpolymers.